2017
DOI: 10.1186/s13722-017-0090-0
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption patterns and HIV viral suppression among persons receiving HIV care in Florida: an observational study

Abstract: BackgroundAlcohol consumption has been associated with poor antiretroviral therapy (ART) adherence but less is known about its relationship to HIV viral suppression, or whether certain drinking patterns have a stronger association than others. The objectives of this study were to determine the association of different patterns of alcohol consumption to HIV viral suppression and ART adherence, and to determine whether any associations of alcohol with HIV viral suppression were mediated by poor ART adherence.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 30 publications
(35 reference statements)
1
49
0
1
Order By: Relevance
“…(19) Research in different realities has already shown that alcohol use decreases compliance with antiretrovirals. (20)(21)(22) The reports obtained in this study demonstrate that participants decided to discontinue treatment to consume alcohol and/or other drugs.…”
Section: Discussionmentioning
confidence: 68%
“…(19) Research in different realities has already shown that alcohol use decreases compliance with antiretrovirals. (20)(21)(22) The reports obtained in this study demonstrate that participants decided to discontinue treatment to consume alcohol and/or other drugs.…”
Section: Discussionmentioning
confidence: 68%
“…Similar results were found in Zimbabwe, where 49.5% of female sex workers had viral loads of <1000 copies/ml [ 34 ]. We defined VLS as <1000 copies/ml, however other studies have used different thresholds, therefore we conducted a sensitivity analysis varying the definition of VLS[ 35 , 36 ]. In Uganda, low service utilization as evidenced by the limited number of women on ART appears to be a major contributing factor in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we used a dichotomous measure of any heavy episodic drinking, based on report of consuming 6 or more drinks on at least 1 occasion in the past year, using the third AUDIT‐C question (including affirmative responses of “less than monthly” to “daily or almost daily”). This measure is strongly associated with increased risk of AUD, as well as poor HIV‐related outcomes …”
Section: Methodsmentioning
confidence: 99%